VJEŠTICE U SUVREMENIM NARATIVIMA NA PODRUČJU BOSNE I HERCEGOVINE (Philological Studies, 2019)
Stories on witches and witchcraft can be traced back to the earliest historical records. In this paper, we will try to answer questions such as, who witches are/were, what are the historical, sociological or psychological reflections on witches and witchcraft, and how have witches been represented in Croatian storytelling, with special emphasis on modern narratives on the territory of Bosnia and Herzegovina. Field research and records of modern narratives among Croats in Bosnia and Herzegovina have proved that storytelling about witches is still very much alive. Such stories mostly tell of old, ugly women who can turn into various creatures (often flies or cats) and wreak havoc onto villages. Numerous and various modern narratives on witches have proven that the mythological-demonic theme is a recurrent theme; neither modern ways of life nor the effects of Christianity could have them suppressed from people’s consciousness.
Keywords: witches, historical and theoretical backgrounds, modern narratives of Croats in Bosnia and Herzegovina